Putting a Non-Essentialist Ontology to Work: A Response to Peter Dahlgren’s Review of The Discursive-Material Knot: Cyprus in Conflict and Community Media Participation - Carpentier, Nico (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
A response to Peter Dahlgren’s review of The discursive-material knot: Cyprus in conflict and community media participation.